The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0104-6632.20140314s00002473
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of di-rhamnolipid produced by Pseudomonas aeruginosa TMN

Abstract: -Pseudomonas aeruginosa TMN was used to produce rhamnolipid (RL) from a variety of carbon and nitrogen substrates. The most favorable carbon sources for RL production were glucose and glycerol (both at 40 g/L), giving a RL yield of 0.3 and 0.25 g/L, respectively. Meanwhile, sodium nitrate appeared to be the preferable nitrogen source, resulting in a RL production of 0.34g/L. Rhamnolipid production from P. aeruginosa TMN was affected by temperature, pH and agitation rate, with 37 °C, pH 7 and 200 rpm agitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 68 publications
3
34
0
2
Order By: Relevance
“…The bacterium was isolated from soils with hydrocarbon contaminated industrial zone and identified as a P. aeruginosa (ESOGÜ‐BK B 053). Seed culture was incubated in nutrient broth at overnight and then rhamnolipid production was performed in mineral salt medium (MSM) consisting of (g/L) NH 4 Cl 15 g, KH 2 PO 4 4.3 g, K 2 HPO 4 3.4 g, KCl 1.1 g, NaCl 1.1 g, yeast extract 0.5 g, CaCl 2 · 2H 2 O 0.24 g, ZnSO 4 · 7H 2 O 0.29 g, MnSO 4 · H 2 O 0.17 g, MgSO 4 · 7H 2 O 0.5 g. For this purpose, the seed culture (2% inoculum) was inoculated and incubated at 35°C and 150 rpm for 72 h. Carbon source for this medium was added as 20 g/L sucrose. The pH of mineral salt medium has not been adjusted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterium was isolated from soils with hydrocarbon contaminated industrial zone and identified as a P. aeruginosa (ESOGÜ‐BK B 053). Seed culture was incubated in nutrient broth at overnight and then rhamnolipid production was performed in mineral salt medium (MSM) consisting of (g/L) NH 4 Cl 15 g, KH 2 PO 4 4.3 g, K 2 HPO 4 3.4 g, KCl 1.1 g, NaCl 1.1 g, yeast extract 0.5 g, CaCl 2 · 2H 2 O 0.24 g, ZnSO 4 · 7H 2 O 0.29 g, MnSO 4 · H 2 O 0.17 g, MgSO 4 · 7H 2 O 0.5 g. For this purpose, the seed culture (2% inoculum) was inoculated and incubated at 35°C and 150 rpm for 72 h. Carbon source for this medium was added as 20 g/L sucrose. The pH of mineral salt medium has not been adjusted.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterium was isolated from soils with hydrocarbon contaminated industrial zone and identified as a P. aeruginosa (ESOG € U-BK B 053). Seed culture was incubated in nutrient broth at overnight and then rhamnolipid production was performed in mineral salt medium (MSM) consisting of (g/L) NH 4 [19,20] and incubated at 35°C and 150 rpm for 72 h. Carbon source for this medium was added as 20 g/L sucrose. The pH of mineral salt medium has not been adjusted.…”
Section: Production Of Rhamnolipidmentioning
confidence: 99%
“…In this work complex media components for cultivation of P. aeruginosa PAO1 have been screened for identifying their specific roles to produce biosurfactant and pigment. Screening of components of complex cultivation media with statistical analysis helps us to understand the effects of each component on biomass growth, product formation and underlying metabolic changes responsible for such variation (Das et al, 2009;Moussa et al, 2014). As carbon source is essential for growth and product formation, glycerol was used since it is available in excessive amount at a cheap price as a by-product from the biodiesel industry (Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnolipids are efficient in the bioremediation of soils polluted by oily compounds (Santa Anna et al, 2007). According to Pirollo (2006) and Moussa et al (2014), rhamnolipids consist of one or two rhamnose molecules and one or two fatty acid chains of 8 to 12 carbon atoms, which may be saturated or unsaturated.…”
Section: Introductionmentioning
confidence: 99%